Implementation of a biopsy protocol to improve detection of esophageal eosinophilia: a Danish registry-based study - Krarup, Anne Lund; Drewes, Asbjørn Mohr; Ejstrud, Per; Laurberg, Peter Thaysen; Vyberg, Mogens (Endoscopy, 2020)
Background In the North Denmark Region (580 272 inhabitants), only 0–4 cases of possible eosinophilic esophagitis (EoE) were identified annually in 1999–2010, suggesting underdiagnosis. This study aimed to increase the diagnosis of EoE by introducing a regional biopsy protocol for patients with dysphagia.Methods In 2011, leaders of regional endoscopy units attended a consensus meeting where a biopsy protocol was proposed. The national pathology registry was used to identify patients with esophageal eosinophilic inflammation during 2007–2017.Results Discussion resulted in consensus on a protocol to take eight biopsy samples in dysphagia patients (four biopsies from 4 cm and 14 cm above the esophagogastric junction–“4–14–4 rule”) regardless of the macroscopic appearance, and to code eosinophilia systematically in the pathology registry. A pictogram showing the 4–14–4 rule was sent to all endoscopy units. The number of patients with esophageal eosinophilia detected per year increased 50-fold after the protocol was implemented in 2011 (median of 1 [interquartile range 0–3] vs. 52 [47–56]; P < 0.001), and the number of biopsy samples per patient doubled (median 4 [4–5] vs. 8 [6–9]; P < 0.04). Of 309 patients diagnosed with esophageal eosinophilia in 2007–2017, 24 % had erosive esophagitis or Barrett’s esophagus, and 74 % had EoE.Conclusions A consensus-based biopsy protocol and improved coding of eosinophilia in the pathology registry resulted in a 50-fold increase in patients diagnosed with esophageal eosinophilia/year. These patients can now receive treatment. The effort to establish the protocol and change the culture of endoscopists and pathologists was minimal.